2013
DOI: 10.1111/1462-2920.12194
|View full text |Cite
|
Sign up to set email alerts
|

A morphogenetic survey on ciliate plankton from a mountain lake pinpoints the necessity of lineage‐specific barcode markers in microbial ecology

Abstract: Analyses of high-throughput environmental sequencing data have become the ‘gold-standard’ to address fundamental questions of microbial diversity, ecology and biogeography. Findings that emerged from sequencing are, e.g. the discovery of the extensive ‘rare microbial biosphere’ and its potential function as a seed-bank. Even though applied since several years, results from high-throughput environmental sequencing have hardly been validated. We assessed how well pyrosequenced amplicons [the hypervariable eukary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 88 publications
5
122
0
Order By: Relevance
“…Microscopy results are shown for dimensions compared with the pore size used for sample filtering or primer mismatches is not evident, but there could be other PCR bias (for example, selective amplification of closely-related species), taxon-specific susceptibility to DNA extraction or variability in the copy number of the rDNA operon (Medinger et al, 2010;Heywood et al, 2011). This supports known inconsistencies in relative abundances estimated by HTS and microscopy for ciliates and other protists (Bachy et al, 2013;Egge et al, 2013;Santoferrara et al, 2014;Stoeck et al, 2014).…”
Section: Comparison Of Tintinnid Morphospecies and Otussupporting
confidence: 54%
“…Microscopy results are shown for dimensions compared with the pore size used for sample filtering or primer mismatches is not evident, but there could be other PCR bias (for example, selective amplification of closely-related species), taxon-specific susceptibility to DNA extraction or variability in the copy number of the rDNA operon (Medinger et al, 2010;Heywood et al, 2011). This supports known inconsistencies in relative abundances estimated by HTS and microscopy for ciliates and other protists (Bachy et al, 2013;Egge et al, 2013;Santoferrara et al, 2014;Stoeck et al, 2014).…”
Section: Comparison Of Tintinnid Morphospecies and Otussupporting
confidence: 54%
“…HTS surveys provide a detailed picture of the taxa present in the community, including rare species in the assemblage (18,33), and reveal diversity not evident using other methods. However, the interpretation of the HTS signal in terms of total cell abundances is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the few sequences obtained did not represent the dominant observed species, a clear sign of the biases in this molecular approach. More recent comparative studies used HTS, and therefore were not limited by the sequencing effort but focused on specific taxa, in particular marine and freshwater ciliates (2,(16)(17)(18). Ciliate species have the advantage of having conspicuous morphological traits…”
mentioning
confidence: 99%
“…Stoeck et al (2014) found many quantitative and qualitative differences between amplicons and morphotypes. They saw that taxon abundance from amplicon data did not necessarily track morphotype abundance.…”
Section: Discussionmentioning
confidence: 99%